Successful treatment using apatinib in intractable brain edema: A case report and literatures review. Issue 12 (2nd December 2018) - Song, Yanqiu; Liu, Bailong; Guan, Meng; Liu, Min
ABSTRACT: The treatment of intractable vasogenic brain edema (VBE) caused by tumor and irradiation is challenging. Traditional intervention strategy includes dehydration and glucocorticoids accompanied by obvious side effects and minor effects after long-term use. Novel treatment needs to be found urgently. Recently, vascular endothelial growth factor (VEGF)/VEGFR pathway has been revealed to be essential in VBE. Therefore, tyrosine kinase inhibitor (TKI) targeting VEGFR which blocks (VEGF)/VEGFR signal might be effective. However, such reports have seldom been described. Herein, we documented a heavily-treated breast cancer patient experienced progressive aphasia, limb activity disorder and intermittent convulsion 10 months after radiotherapy of brain metastasis (BM). Cranial MRI demonstrated large peritumoral brain edema (PTBE). High dose of steriods and dehydration had no improvement. Apatinib with a dose of 250mg daily was initiated and all her discomforts disappeared after 10 days of use. The brain MRI of taking apatinib 5 weeks demonstrated remarkable shrinkage of edema. Our case indicates that apatinib, a potent small-molecular TKI targeted VEGFR2 is promising for intractable VBE for satisfactory efficacy and safety. This case is of great value in its rarity and because it provides new insight into PTBE management in clinical practice.